Identification of the CaCRT gene family and function of CaCRT1 under low-temperature stress in pepper (Capsicum annuum L.) - Yanzhuang Wang; Ping Yang; Jian Li; Juan Li; Keyan Zhu; Minkun Pei; Jie Li; Hongbin Du (Scientific Reports)
Abstract To explore CRT gene family members and their responses to low-temperature stress, bioinformatics methods were used to identify the CRT gene family in pepper. In this study, a total of 4 CRT gene family members were identified by screening. The genes were found to be located on different chromosomes, and phylogenetic tree and collinearity analyses were performed. In addition, the cis-acting elements identified in the 2.0 kb upstream promoter regions of the 4 CaCRTs described in this study can be divided into three categories. The expression patterns of CRTs in different tissues and organs under low-temperature stress were analysed. Virus-induced gene silencing (VIGS) technology was used to verify the function of CaCRT1, and the results revealed that CaCRT1 participated in the pepper response to low-temperature stress and the accumulation of excessive reactive oxygen species (ROS) and malondialdehyde (MDA). In summary, this study systematically verified the regulatory role of CaCRT gene family members in pepper under low-temperature stress and provided a foundational understanding for further research on the biological functions of pepper CRT genes.